Interpretasi Data Geomagnet Untuk Menentukan Keberadaan Pipa Air Bawah Permukaan Bumi (Studi Kasus: Lingkungan Masjid Al-Musannif Kampus IV UINSU): (Studi Kasus: Lingkungan Masjid Al-Musannif Kampus IV UINSU) - Meilita Rahma; Ratni Sirait; Lailatul Husna Lubis (Jurnal Teori dan Aplikasi Fisika, 2024)
The existence of subsurface water pipes in the Al-Musannif Mosque environment, Campus IV UINSU, must be established. This is because it is one of the important roles of knowing the location of the pipes in order to reduce engineering accidents and as the accuracy of engineering surveys. This research was conducted using the geomagnetic method, which aims to determine the location of subsurface water pipes and to find out how the subsurface structure in the region is constructed. From this measurement, 43 points were obtained with a distance of 5 to 10 meters and with coordinates from latitude 3°49'56.24 "N and longitude 98°58'72.13" E to latitude 3°49'49.50 "N and 98°58'58.12 "E. The results of this study indicate the presence of anomalous values throughout the study area, exhibiting an elongated shape with a dominant northeast-southwest direction. The values range from 5.6 to 321.1 nT, which is thought to be associated with subsurface pipelines. The 2D modeling results indicate the presence of two anomalies: a high anomaly, which is thought to be a pipe, and a low anomaly, which is suspected to be clay lithology. At high susceptibility contrast values, ranging from 0.2 to 1 SI, with a depth of 2 to 4 m below the surface, it is postulated that these anomalies are associated with metal pipes located in the northwest and southeast. At low susceptibility contrast values, ranging from -1 to -0.2 SI, with a depth of 0 to 20 m below the surface, it is proposed that these anomalies are associated with clay marked with dark blue to light blue color.   Keywords: magnetic field anomalies, geomagnet, subsurface structure, susceptibility